Synthesis, in vitro ADME profiling and in vivo pharmacological evaluation of novel glycogen phosphorylase inhibitors. Issue 14 (15th July 2020) - Miao, Guang-xin; Wang, You-de; Yan, Zhi-wei; Zhang, Li-ying
Graphical abstract: Abstract: A small set of indole-2-carboxamide derivatives identified from a high-throughput screening campaign has been described as a novel, potent, and glucose-sensitive inhibitors of glycogen phosphorylase a (GPa). Among this series of compounds, compound 2 exhibited moderate GP inhibitory activity (IC50  = 0.29 μM), good cellular efficacy (IC50  = 3.24 μM for HepG2 cells and IC50  = 7.15 μM for isolated rat hepatocytes), together with good absorption, distribution, metabolism, and elimination (ADME) profiles. The in vivo animal study revealed that compound 2 significantly inhibited an increase of fasting blood glucose level in adrenaline-induced diabetic mice.